Historical itinerary through the Laurent &Cía photographic library (1850-1900) - Pérez Gallardo, Helena (Anales de Historia del Arte, 2016)
In the year of the bicentenary of the birth of Jean Laurent and Minier (1816-1886), one of the most outstanding and certainly the most productive photographer of nineteenth-century Spain, we propose the updating of a figure and its commercial firm that has focused much of our research and whose portrait has also been completed by other significant contributions the last years.